Assessment of Mental Health Problems of School Children Using Self Report Strengths and Difficulties Questionnaire - Chhetri, Uma D; Lamichane, Anita; Pokhrel, Shami; Sharma, Bhaskar (Journal of Lumbini Medical College, 2021)
Introduction: Psychological disorders among children and adolescents are the least discussed health problems in pediatrics. There is limited data on the prevalence of mental health problems among adolescents in low-income countries like Nepal. This study intended to find the prevalence of mental health problems among school children in a secondary school in western Nepal. Methods: In this descriptive cross-sectional study, students of grades six to eleven of two private schools of a district in Nepal were randomly selected. The self-rated version of Goodman’s Strength and Difficulty Questionnaire were used to assess mental health problem in these adolescents. Outcomes were measured in a scale of zero to 10 for each of emotional, conduct, hyperactivity, peer problem and pro-social behavior. Difficulty scale and its impact on life were also measured. Results: Out of 902 students, 5% (n=49) had significant and 14% (n=127) had probable mental health problem. Peer problems was the commonest (25%) followed by emotional (15%) and conduct problem (15%) and hyperactivity and pro-social problems were seen in 7% each. Boys had more mental health problem than girls except emotional problem. Mental health problem was more common in lower grade or younger age students. Its impact on life were 0-7.4%. Abnormal internalizing and externalizing problems were reported in 20% and 11% respectively. Conclusion: Mental health problem was prevalent (5 to 25%) in secondary school children. Screening school children for the same would be beneficial for early diagnosis.